2002
DOI: 10.1073/pnas.032468199
|View full text |Cite
|
Sign up to set email alerts
|

Casein kinase I phosphorylates and destabilizes the β-catenin degradation complex

Abstract: Wnt signaling plays a key role in cell proliferation and development. Recently, casein kinase I (CKI) and protein phosphatase 2A (PP2A) have emerged as positive and negative regulators of the Wnt pathway, respectively. However, it is not clear how these two enzymes with opposing functions regulate Wnt signaling. Here we show that both CKI␦ and CKI interacted directly with Dvl-1, and that CKI phosphorylated multiple components of the Wnt-regulated ␤-catenin degradation complex in vitro, including Dvl-1, adenoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
218
2
2

Year Published

2002
2002
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(232 citation statements)
references
References 25 publications
10
218
2
2
Order By: Relevance
“…It has long been known that CK1 isoforms play crucial roles in the Wnt/β‐catenin signalling 28, 29, 30, 34, 35, 43, 44, 45, 46. In fact, early observations that overexpression of CK1 isoforms in Xenopus embryos caused axis duplication suggested a positive role for CK1 in Wnt signalling 47.…”
Section: Discussionmentioning
confidence: 99%
“…It has long been known that CK1 isoforms play crucial roles in the Wnt/β‐catenin signalling 28, 29, 30, 34, 35, 43, 44, 45, 46. In fact, early observations that overexpression of CK1 isoforms in Xenopus embryos caused axis duplication suggested a positive role for CK1 in Wnt signalling 47.…”
Section: Discussionmentioning
confidence: 99%
“…An important biological function of the CKI family is a regulatory role in the Wnt/Frizzled/b-catenin pathway (Gao et al, 2002;Hino et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, our results showed that JCV T-antigen binds to bcatenin through its transcriptional activation domain, and this interaction may stabilize b-catenin. In this respect, stabilization of b-catenin may occur in the following ways: (i) JCV T-antigen bound to the Cterminal of b-catenin peptide forms a structural barrier to prevent APC, CK1, and GSK-3b from binding to and phosphorylating the N-terminus of b-catenin, an event that promotes b-catenin ubiquitination (Polakis, 2000;Gao et al, 2002); (ii) interaction of JCV T-antigen with APC that can inhibit its activity by blocking the association of APC with b-catenin for the degradation complex; (iii) T-antigen-induced downregulation or inhibition of the activity of GSK-3b and CK1 by Tantigen, so that GSK-3b and CK1 may not phosphorylate b-catenin for the degradation process; and (iv) translocation of the JCV T-antigen : b-catenin complex into the nucleus, so that b-catenin will not be degraded in the cytoplasm. At present, our data indirectly favor a role for T-antigen in blocking b-catenin from degradation, and nuclear import of b-catenin through the association with T-antigen.…”
Section: Discussionmentioning
confidence: 99%
“…At this stage, a cell strongly controls its b-catenin concentration by using the adenomatous polyposis coli APC, which binds to excess amounts of b-catenin. This interaction promotes phosphorylation of b-catenin via its N-terminus by CK1 and GSK-3b (Polakis, 2000;Gao et al, 2002). The phosphorylated b-catenin, in turn, undergoes degradation by the ubiquitin-mediated pathway (Polakis, 2000).…”
Section: Introductionmentioning
confidence: 99%